The influence of chemicals on the development and viability of Trichuris vulpis nematode eggs isolated from infested dogs - Yevstafieva, V.; Dolhin, O.; Melnychuk, V.; Dedukhno, A.; Pishchalenko, M.; Krasota, O. (Regulatory Mechanisms in Biosystems, 2023)
Preventive measures against invasive diseases should be carried out taking into account the peculiarities of the life cycle of helminths. This is especially relevant for geohelmintiases, where the infection is mainly transmitted via environmental objects contaminated with the pathogen at the exogenous stages of the parasite’s development. It has been proven that among the causative agents of nematodoses of the gastrointestinal tract of animals, the eggs of geohelminths of the genus Trichuris are the most resistant to the action of disinfectants. The aim of the research was to establish in laboratory conditions the ovicidal effect of chemicals on the development and viability of Trichuris vulpis nematode eggs isolated from infested dogs. Two disinfectants were tested in vitro, Arquades-plus (dialkyl dimethyl ammonium chloride, dodecyl dimethyl ammonium chloride, tetrasodium salt) and Brovadez-plus (alkyl dimethyl benzyl ammonium chloride, dodecyl dimethyl ammonium chloride). Arquades-plus disinfectant showed a high level of ovicidal efficiency (94.0%) only at the maximum concentration and exposure (2.0%, 60 min), and 4.7% of nematode eggs in the test culture remained viable. Brovadez-plus disinfectant was less effective and did not provide a high level of ovicidal efficiency against Trichuris eggs in the studied concentrations and exposures. Satisfactory and unsatisfactory levels of its ovicidal effect (63.1–77.1% and 2.5–58.9%) were established when using the product in concentrations of 2.0% and 0.5–1.5%, respectively, for exposures of 10–60 min. The disinfestation activity of the preparations was characterized by metric changes in experimental test cultures compared to the control test culture. Under the influence of Arquades-plus at all concentrations, the length of the eggs was greater (by 0.4–2.0%), and the width was smaller (by 0.7–4.9%). Under the influence of Brovadez-plus in concentrations of 1.0–2.0%, the length of the eggs was greater (by 0.5–0.9%), the width was smaller (by 0.3–4.1%). The results of the conducted studies allow us to recommend the Arquades-plus disinfectant in a 2.0% concentration (exposure of 60 minutes) for effective control and prevention of infection of dogs with the causative agent of trichurosis.